Evaluation Of Andrographis Paniculata, Eurycoma Longifolia And Phyllagathis Rotundifolia For Antimalarial Activity Against Chloroquine And Mefloquine Resistant Malarial Parasites - Che Husin, Che Nasriyyah (2010)
The emergence of drug resistant malaria parasite is one of the major health problems in the world and the search for new treatment is increasingly becoming a priority. Kemunculan parasit malaria yang rintang terhadap ubat merupakan salah satu daripada masalah kesihatan yang utama di dunia dan pencarian rawatan baru adalah suatu keutamaan.